2000
DOI: 10.1074/jbc.m003053200
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Acetylcholine Receptors Induce the Expression of the Immediate Early Growth Regulatory Gene CYR61

Abstract: In brain, muscarinic acetylcholine receptors (mAChRs) modulate neuronal functions including long term potentiation and synaptic plasticity in neuronal circuits that are involved in learning and memory formation. To identify mAChR-inducible genes, we used a differential display approach and found that mAChRs rapidly induced transcription of the immediate early gene CYR61 in HEK 293 cells with a maximum expression after 1 h of receptor stimulation. CYR61 is a member of the emerging CCN gene family that includes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 75 publications
3
50
0
Order By: Relevance
“…This suggested that the mechanism of the M 3 -muscarinic receptor response was rapid in its onset and was then maintained for an extended period after agonist withdrawal. A strong candidate for mediating such a mechanism was rapid changes in intracellular calcium, which in the case of a number of GPCRs has been shown to encode for longer adaptive responses such as changes in gene transcription (24,25). However, analysis of a truncated mutant of the M 3 -muscarinic receptor (⌬565-M 3 ), which was unable to mediate an anti-apoptotic response, revealed that this receptor was still coupled to the calcium/PLC pathway in a manner similar to the wild-type receptor.…”
Section: Anti-apoptotic Response Of G Q/11 -Coupled Muscarinicmentioning
confidence: 99%
“…This suggested that the mechanism of the M 3 -muscarinic receptor response was rapid in its onset and was then maintained for an extended period after agonist withdrawal. A strong candidate for mediating such a mechanism was rapid changes in intracellular calcium, which in the case of a number of GPCRs has been shown to encode for longer adaptive responses such as changes in gene transcription (24,25). However, analysis of a truncated mutant of the M 3 -muscarinic receptor (⌬565-M 3 ), which was unable to mediate an anti-apoptotic response, revealed that this receptor was still coupled to the calcium/PLC pathway in a manner similar to the wild-type receptor.…”
Section: Anti-apoptotic Response Of G Q/11 -Coupled Muscarinicmentioning
confidence: 99%
“…Phorbol ester 12-O-tetradecanoyphorbol-13-acetate (TPA) mediates Cyr61 expression in the liver (Nathans et al, 1988). Incidentally, others and we have found expression of Cyr61 involving protein kinase C (PKC) and the MEK/MAPK pathways (Chung and Ahn, 1998;Inuzuka et al, 1999;Albrecht et al, 2000;Tsai et al, 2001, manuscript submitted). Cyr61 is also vitamin D-responsive in human osteoblasts and osteosarcoma cell lines (Scheutze et al, 1998).…”
mentioning
confidence: 99%
“…Other cytokines, such as tumor necrosis factor a (TNFa) and interleukin-1 (IL-1) also strongly elevate the expression of Cyr61 (Scheutze et al, 1998). Cyr61 is di erentially expressed by muscarinic acetylcholine receptors (mAChRs) in the brain (Albrecht et al, 2000), and by factor VIIa and thrombin in human ®broblasts (Pendurthi et al, 2000). Phorbol ester 12-O-tetradecanoyphorbol-13-acetate (TPA) mediates Cyr61 expression in the liver (Nathans et al, 1988).…”
mentioning
confidence: 99%
“…Within 1 h of M 1 receptor activation, the expression of immediate early genes is induced. These genes play important roles in coupling receptor stimulation to long-term neuronal responses (Albrecht et al, 2000). Three hours after M 1 receptor activation, a significantly higher number of genes, some expressing differential patterns, were observed.…”
Section: Introductionmentioning
confidence: 99%